Perceived Value: Definitions, Concepts and Measures for Sport And Fitness Industry - Hüseyin Çevik; Ali Sevilmiş (Türk Spor ve Egzersiz Dergisi)
In this study, it is aimed to provide a framework about approaches to the measurement of perceived value in sports and fitness studies. In order to achieve this goal, the definition, conceptual approaches, dimensions and measurement approaches of perceived value were examined. In the context of sports in general and fitness in particular, its relationship with components such as service quality, satisfaction, and behavioral attitudes, which are examined in relation to value, was discussed. In related studies, the concept of perceived value has been measured in a uni-dimensional and multi-dimensional way. Perceived value may differ according to product, service, and consumer characteristics. Since sports consumers are a group of people whose consumption characteristics differ as active and passive participants (spectators and fans), the differentiation of the measurement of perceived value is an acknowledged situation. It was attempted with this study to provide a deeper understanding of the nature of perceived value for researchers in the field of sports and fitness. In addition, recommendations for future studies in the contexts of sports and fitness were presented.